Indonesia's Digital Security Strategy: Countering the Threats of Cybercrime and Cyberterrorism - Khoirunnisa, Khoirunnisa; Jubaidi, Didi (Politeia : Journal of Public Administration and Political Science and International Relations, 2024)
Cybercrime is becoming a very serious threat to Indonesia's national security. The pervasive nature of cyberattacks raises questions about the effectiveness of current regulatory measures. This research aims to analyze how the government addresses security challenges in cyberspace in a sustainable manner. A descriptive qualitative method was used to evaluate the impact of cybercrime in Indonesia and its relationship with highly interrelated regulations. The results show that the threat of cybercrime and cyber-terrorism, in both physical and digital forms, has increased alarmingly in recent years. The impact of universal access to all relevant information has several consequences, including the spread of false information and the development of cybercrime networks. Significant measures are needed to disrupt the cyber terrorism industry to create a safe environment in Indonesia. The success of regulatory measures in Indonesia relies on a holistic approach involving the active participation of the government, society, and the private sector.